Perbedaan kemampuan shooting pemain depan, tengah, dan belakang pada tim sepakbola liga 3 Persikama - Cahyono, Rifki Dwiadi; Syaukani, Agam Akhmad (Jurnal Porkes, 2023)
This study aims to investigate and determine the quality differences in the shooting ability of Persikama's forwards, midfield players, and defenders. The core of the problem of this study is that the difference in shooting ability between the front, middle and back players is unknown, researchers measure aspects of accuracy and speed. This research is of a quantitative type with a comparative descriptive method because it compares the shooting abilities of soccer players in 3 different positions. The number of subjects of this study were 15 players. Researchers used observation and shooting ability tests as data collection instruments. The data analysis technique used to test the hypothesis is ANOVA. Based on the results of the study, the order of accuracy of the first player's shooting ability from the best is the midfielder, defender and forward player. While the order of the speed of the best shooting ability is the front player, the back player, and the mid player. Although the results of the ANOVA test prove that the probability value obtained for each is more than a significance value of 0.05, thus indicating or concluding that there is no significant difference in the shooting abilities of the fore-players, midfield players and persikama defenders